(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2019)
This study will examine some of the figures of desire in the sonnets by the mexican poet Jorge Cuesta (1903-1942) from a literary, psycho-analitical and philosophical angle. The purpose is to bring to prominence that, in Cuesta’s poetical world, “at the game of desire the dice are loaded and the cards are fixed”, as Françoise Dolto says. We will bring out the poetical forms expressing the most significant figures of desire. We will observe how the poetic voice is pursuing an unattainable and elusive object of desire which vanishes at the very moment when it seems within reach. The construction of the sonnets, whit its framework of poetical images, shows the tension between desire and fulfilment and thus reveals the existential drama the speaker goes through. A similar situation to Jorge Cuesta’s own tragedy.